Thoracoscopic versus open repair of CDH in cardiovascular stable neonates - Costerus, Sophie; Zahn, Katrin; Wessel, Lucas (Surgical endoscopy and other interventional techniques, 2016)
Background: Thoracoscopic surgery is an increasingly popular surgical technique to repair congenital diaphragmatic hernia (CDH). However, acidosis during surgery and the higher recurrence rate are considerable risk factors. The aim of this retrospective study is to compare the outcome of open versus thoracoscopic repair of the diaphragm in neonates with CDH with the same degree of cardiovascular and pulmonary illness who meet the criteria for thoracoscopic repair. Methods: Retrospective analysis of all patients of two large national reference centers for CDH born in the years 2008 through 2012, and meeting the criteria for surgical repair on cardiopulmonary and physiological criteria according to the CDH EURO consortium consensus and meeting the criteria for thoracoscopic repair according to the review by Vijfhuize et al. The surgical technical aspects were comparable in both centers. Results: 108 patients were included, of whom 75 underwent thoracoscopic repair and 34 underwent open repair. The gestational age and lung-to-head ratio were significantly lower and stay on the ICU significantly longer in the open-repair group. The operation time was longer (178 vs. 150 min, p = .012) and the recurrence rate higher (18.9 vs. 5.9 %, p = .036) in the thoracoscopic-repair group. The arterial pH, pO2, pCO2 and base excess before and after thoracoscopic repair were all significantly different. Conclusion: After critical selection for thoracoscopic repair of left-sided CDH based on the patient’s preoperative condition, the outcomes of open repair were almost identical to those of thoracoscopic repair. A notable exception is the recurrence rate, which was significantly higher in the thoracoscopic-repair group. For the time being, thoracoscopic primary closure seems a safe and effective procedure, but efficacy of thoracoscopic patch repair has not been established.